Synthesis of polyaniline nanomaterials for an effective supercapacitor applications - Melese Yalew Ayalew; Endrias Adane Bekele; Fekadu Melak; Lodrick Monieko Wangatia; Olu Emmanuel Femi; Tessera Alemneh Wubieneh; Addisu Alemayehu Assegie; Getinet Yenealem Ashebir; Delele Worku Ayele; Ababay Ketema Worku; Minbale Admas Teshager; Tadele Ageru Alemu; et al. (Materials Research Express)
Polyaniline-based materials have been widely used for supercapacitors due to their outstanding properties, such as high specific capacitance, excellent electrochemical properties, and ease of synthesis methods; however, the short-cycle stability of PANI-based supercapacitors and swelling and shrinking of polymeric structures limit their commercialization. Herein, we synthesized polyaniline (PANI) nanomaterials, which meet high specific capacitance through the chemical oxidative polymerization of aniline with ammonium persulfate (APS) in aqueous salicylic acid. The electrode materials were characterized using UV–vis, TGA, SEM, XRD, BAS-50 W potentiostat, and FTIR instrumentations. The electrical conductivity of the prepared materials was analyzed and found to be relatively high. The electrochemical supercapacitance performance of PANI nanomaterials was characterized using cyclic voltammetry. The polyaniline nanomaterials with a [salicylic acid]/[aniline] molar ratio of 0.8 showed a maximum specific capacitance of 688.5 Fg-1 at a scan rate of 50 mV s ^−1 . Polyaniline nanomaterials were found to exhibit better specific capacitance when compared to bulk polyanilines. Thus, PANI nanomaterials have been found to be a promising alternative for supercapacitor applications.